(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
The article dwells on structural models of comparison as a stylistic device in the English and Tajik languages and an eduction of the following thematic groups such as the images of characters, appearance, internal condition, status / position.